Penyelenggaraan Pendidikan untuk Pembangunan Berkelanjutan di Sekolah Dasar - Hafizah Ghany H (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2018)
This paper reviews the implementation of education for sustainable development (EfSD). It includes the definitions of sustainable development, education for sustainable development, and its implementation at elementary school level. EfSD concept integrate learning strategy with knowledge (about social, economy, environment), issues, skill, perspectives and values on sustainable development. EfSD can stimulate changes in the perspectives of people, inspiring them to create a safer, healthier, and sustainable life. Educational policy in Indonesia about graduate competence and content standard for elementary students has in line with EfSD concept. Some school in Indonesia has already integrate EfSD concept on their learning process, but based on the results, the process still need some improvement.